Sources notable selections in mass media - Hanson, Jarice; Maxcy, David J.
This book brings together 40 selections of enduring intellectual value--classic articles, book excerpts, and research studies--that have shaped the study of mass media and our contemporary understanding of it. Sources provides the opportunity for readers to encounter many of the greatest thinkers in mass media at first hand. The book includes carefully edited selections from the works of the most distinguished observers of the mass media, past and present, from Harold D. Lasswell, Hadley Cantril, and Neil Postman to Kathleen Hall Jamieson, Michael Eric Dyson, and Annette Kuhn.